What is my block cave worth? Valuing risk in block cave mining - Dudley, J.-A. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
As a wider variety of orebodies are evaluated for their suitability for the block cave mining method, engineers must clearly articulate the associated value proposition. While the method’s low operating costs and high productivities – driven by efficient mining systems and substantial mining blocks – are attractive, the economic assessment is often complex due to significant capital requirements, lengthy development timelines, and numerous modifying factors. Engineers are adept at quantifying risk within ore reserve estimates, factoring in elements such as dilution, early drawpoint collapse, boundary drawpoint losses, and cave wall underbreak. While the associated capital cost ranges and variability in construction and ramp-up schedules can be communicated, the combined message is not always fully appreciated by stakeholders. The scale of costs and production inherent to block caving means that a project’s economics can be significantly affected if multiple risks materialise during execution and early ramp-up phases. To achieve what is perceived as a realistic outcome, study teams may be inclined to incorporate layers of conservatism into ore reserve estimates and production schedules. Within a competitive capital landscape, this approach can result in otherwise robust projects being deprioritised for capital allocation and development. Conversely, overly optimistic assumptions can lead to uncomfortable value write-downs and reductions in ore reserves. Advances in technology now enable the processing of a wide range of inputs to generate multiple project schedules, allowing risk to be considered as a spectrum of possible outcomes. It is essential to engage stakeholders in adopting a mindset that views project risk as a continuum rather than a binary outcome. Drawing on the author’s 30 years of experience in designing, evaluating and operating block cave operations, this paper presents methodologies for valuing risk and highlights key factors that have historically influenced caving project valuations.